Analysis of Goods and Services Expenditure Systems and Procedures Based on Permendagri No. 77 of 2020 at the Manado City Tourism Office - Angelia Parindingan; Hendrik Manossoh; Meily Y. B. Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Good systems and procedures for the implementation of goods and services expenditure procurement are needed to support effective regional financial management so that each agency can carry out its operational activities. This study aims to determine the system and procedures for implementing goods and services expenditures at the Manado City Tourism Office by applicable regulations. The research method used is qualitative descriptive research. Data collection methods through interviews, and documentation. The data analysis process by collecting data, presenting the results of interviews and documentation obtained, studying how systems and procedures operate, conducting an analysis process, and drawing conclusions. The results showed that the implementation of systems and procedures for the procurement of goods and services of the Manado City Tourism Office has been carried out by Permendagri No. 77 of 2020 by involving the functions, duties, and authorities of the parties involved, and has been equipped with documents that are used and can be accounted for, as well as the application system used. It is better to improve the internet network system to expedite work so that the financial reports presented can be submitted on time.